Agriculture for Nutrition and Health: Gender strategy for phase II - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2021)
The challenge of addressing food security is not simply a matter of ensuring that all people have enough food—or energy (calories)—to live a healthy life. A much more daunting problem is to ensure that poor people have access to nutritious1 and high-quality diets. Typically, poor households subsist on monotonous staple-based diets; they lack access to nutritious foods, such as fruits, vegetables, animal source foods (fish, meat, eggs, and dairy products), or wild foods of high nutrient content. Lack of diversity in the diet is strongly associated with inadequate intake and risks of deficiencies of essential micronutrients (Ruel 2003; Leakey 1999; Arimond et al. 2010). The resulting deficiencies have farreaching health and nutrition consequences, both in the short and the long term. Economic constraints, lack of knowledge and information, and related lack of demand for nutritious foods are critical factors that limit poor populations’ access to such foods.